2016
DOI: 10.1148/radiol.2016150719
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Transcatheter Arterial Chemoembolization (TACE) with Ginsenoside Rg3 versus TACE Alone for the Treatment of Patients with Advanced Hepatocellular Carcinoma

Abstract: Purpose To conduct a single-center, open-label, randomized, controlled trial to compare the effectiveness and safety of (a) ginsenoside Rg3 combined with transcatheter arterial chemoembolization (TACE) and (b) TACE alone in patients with advanced hepatocellular carcinoma (HCC). Materials and Methods This trial was approved by the Fudan University Zhongshan Hospital ethics committee and was registered with the Chinese Clinical Trial Registry (ChiCTR-TRC-11001643). After informed consent was obtained, 228 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…In another study, the safety and efficacy of combined ginsenoside Rg3 and transcatheter arterial chemoembolization (TACE) were studied in patients with advanced hepatocellular carcinoma. The results showed that this therapy ameliorated TACE-induced adverse effects and prolonged the overall survival compared to the use of TACE alone [264].…”
Section: Ginsenosidesmentioning
confidence: 96%
“…In another study, the safety and efficacy of combined ginsenoside Rg3 and transcatheter arterial chemoembolization (TACE) were studied in patients with advanced hepatocellular carcinoma. The results showed that this therapy ameliorated TACE-induced adverse effects and prolonged the overall survival compared to the use of TACE alone [264].…”
Section: Ginsenosidesmentioning
confidence: 96%
“…Ginsenoside Rg3 is one of the important ginsenosides in ginseng, the pharmacological effects of which mainly focus on treatment of tumor related diseases. A study showed that Rg3 alleviated the adverse reactions of transcatheter arterial chemoembolization in patients with hepatocellular carcinoma, and prolonged the survival of patients (Zhou et al, 2016). Rg3 can restore endothelial dysfunction against cardiotoxicity by inhibiting oxidative damage and apoptosis via Akt-mediated activation of the NF-E2-related factor 2-antioxidant response element (Nrf2-ARE) pathway injured by adriamycin (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although many clinical trials of TACE alone or targeted agents in combination with TACE use OS as a primary endpoint, it takes a long time before its effects are proved [11][12][13] . Furthermore, the OS benefit is diluted by prolonged post-progression survival [14] , because post-trial treatments such as intra-arterial infusion chemotherapy, sorafenib, or other trial agents (including regorafenib, lenvatinib, or immunotherapy) can have a chance of marked antitumor effect, resulting in longer post-progression survival irrespective both in the testing and control arms.…”
Section: Introductionmentioning
confidence: 99%